A VLSI implementation of elevator control based on finite state machine using Verilog HDL - Lagadapati, Naresh; Karri, Manoj; Vaddineni, Tejaswini; Mahaboob Subhani, Sk; Hari Kishore, K (International Journal of Engineering and Technology, 2018)
In this cutting edge period, lifts have turned into a basic piece of any business or open complex. It encourages the quicker development of individuals and gear between floors. The lift control framework is a standout amongst the most critical perspectives in hardware control module that are utilized as a part of car application. Normally lifts are intended for a particular building considering the fundamental factors, for example, the tallness of the building, the quantity of individuals venturing out to each floor and the normal times of high utilization. The lift framework is composed with various control procedures. This usage depends on FPGA, which can be utilized for a working with any number of floors, with the predetermined sources of info and yields. This controller can be executed for a lift with the required number of floors by just changing a control variable in the HDL code. This approach depends on a calculation which decreases the measure of calculation required, by concentrating just on the pertinent guidelines that enhances the execution of the gathering of lift framework.